(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
The restoration of dentition defects using dental implants is often complicated by severe alveolar bone atrophy. This study evaluates various bone-reconstructive techniques, including "open" sinus lifting, guided bone regeneration (GBR) using bioresorbable membranes, and autogenous bone grafting. The analysis focuses on the anatomical consequences of edentulism and the morphofunctional response of bone tissue to surgical intervention. Our findings suggest that while autogenous grafts remain a gold standard for significant defects, the integration of bioresorbable polylactic acid materials and GBR offers a promising, less invasive alternative for optimizing the implant bed.